Therapeutic Potential of Circular RNAs in Osteosarcoma - Wan, Ben; Hu, Hao; Wang, Renxian; Liu, Weifeng; Chen, Dafu (Frontiers in Oncology, 2020)
Osteosarcoma is the most common malignant bone tumor in children and adolescents. Multi-agent chemotherapy, together with surgical removal of all detectable lesions, has improved the long-term survival rate to 65–70% in patients with localized osteosarcoma and to 25–30% in patients with metastatic osteosarcoma since the 1970s. However, the conventional strategy has not improved in recent decades. With accumulating knowledge of the natural circular RNA (circRNA) pathogenesis of osteosarcoma, the diagnostic and therapeutic potential of some circRNAs has been explored. Meanwhile, artificial circular RNAs have been designed as onco-microRNA inhibitors to exert antitumor functions. Therefore, natural and artificial circular RNAs, like other RNA counterparts, are attractive new classes of therapeutic molecules for the treatment of osteosarcoma. This review summarizes the latest progress in the relationship between circRNAs and the malignant phenotype of osteosarcoma and sheds light on the therapeutic potential of the two types of circular RNA in the clinic.